Densification method of carbon-carbon composite material

Through chemical vapor infiltration pyrolytic carbon densification and graphitization treatment, combined with high-temperature and high-pressure sintering, it solves the problems of high operational risk, high cost and technical difficulty in the carbon-carbon composite material densification process in the existing technology, and achieves material density Significant improvement and improvement in production efficiency.

CN119330738APending Publication Date: 2025-01-21CENT SOUTH UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411565065.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The lack of effective densification processes in the prior art leads to problems such as high operational risks, expensive prices and technical difficulties in the preparation of high-density carbon-carbon composite materials.

Method used

By subjecting the carbon fiber preform to chemical vapor infiltration pyrolysis carbon densification and graphitization, combined with high-temperature and high-pressure sintering, the densification of carbon-carbon composite materials is achieved.

Benefits of technology

This method can significantly increase the density of carbon-carbon composite materials, shorten the production cycle, and reduce production costs without introducing impurities and causing little damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330738A_ABST
    Figure CN119330738A_ABST
Patent Text Reader

Abstract

The invention discloses a densification method of a carbon-carbon composite material, which comprises the following steps: carrying out chemical vapor infiltration pyrolytic carbon densification on a carbon fiber preform to obtain a carbon-carbon green body, graphitizing the carbon-carbon green body to obtain a carbon-carbon composite blank, and sintering the carbon-carbon composite blank at high temperature and high pressure to obtain the carbon-carbon composite material. Densification is achieved through creep deformation of the matrix carbon, namely plastic deformation of the matrix carbon under the high-temperature constant load, and the densification process is simple, easy to regulate and control, small in material damage, free of impurity introduction and beneficial to preparation of the high-performance carbon-carbon composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon-carbon composite materials, and in particular relates to a densification method of a carbon-carbon composite material. Background Art

[0002] Carbon-carbon composites have the advantages of excellent high-temperature performance, low density, good friction performance, good thermal properties, high chemical stability and easy processing, making them of important application value in many fields, such as aerospace, automotive industry, high-temperature furnace linings, chemical equipment, etc.

[0003] High-density carbon-carbon composites have the advantages of higher strength, higher high-temperature corrosion resistance, higher ablation resistance, and higher thermal conductivity. High-density carbon-carbon composites are mainly prepared by hot isostatic pressing and impregnation carbonization, which is a process with high operating risks, high prices, and high technical difficulty. However, there are currently no other effective densification processes, and there are few reports on the densification of carbon-carbon composites. Therefore, it is urgent to develop a simple and efficient method for densification of carbon-carbon composites. Summary of the invention

[0004] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a densification method for carbon-carbon composite materials. The present invention subjects a carbon fiber preform to chemical vapor infiltration pyrolysis carbon densification and graphitization treatment, and then performs high temperature and high pressure sintering, and densification is achieved by matrix carbon creep under high temperature and constant load. The densification method for carbon-carbon composite materials provided by the present invention has a short production cycle, little damage to carbon fibers, no impurities are introduced, and the densification process is simple and easy to control.

[0005] In order to achieve this object, the present invention provides the following technical solutions:

[0006] The present invention discloses a densification method for a carbon-carbon composite material. The method comprises the steps of subjecting a carbon fiber preform to chemical vapor infiltration pyrolysis carbon densification to obtain a carbon-carbon blank, subjecting the carbon-carbon blank to graphitization to obtain a carbon-carbon composite blank, and then subjecting the carbon-carbon composite blank to high temperature and high pressure sintering to obtain the carbon-carbon composite material.

[0007] The inventors have found that by subjecting the carbon-carbon composite blank to graphitization treatment and subjecting it to high temperature and high pressure sintering treatment, the density can be increased without further introducing a carbon source, so that the carbon-carbon composite material can be densified, and the method of densification does not introduce impurities to the material, which causes damage. Therefore, in the actual production process, a certain density is first reached by chemical vapor infiltration pyrolytic carbon densification, and then the density is successively increased by graphitization treatment and high temperature and high pressure sintering, and can be directly used or continued to be densified according to the density situation. Due to the higher the density in the process of chemical vapor infiltration pyrolytic carbon densification, the lower the later efficiency is, and the time required is long. Therefore, the method of the present invention can greatly reduce the time of chemical vapor infiltration pyrolytic carbon densification, improve the efficiency of densification, and reduce production costs.

[0008] Preferably, the temperature of chemical vapor infiltration pyrolytic carbon densification is 900-1500°C, preferably 1000-1200°C, and the furnace pressure is 0.3-4.0 KPa.

[0009] Preferably, the carrier gas for chemical vapor infiltration pyrolysis carbon densification is argon, and the carbon source gas is propylene and / or methane, preferably propylene and methane; wherein the volume ratio of the carrier gas to the carbon source gas is 1-4:1.

[0010] Further preferably, when the carbon source gas is propylene and methane, the volume ratio of propylene to methane is 0.05-0.2:1;

[0011] The inventors found that using propylene and methane as carbon source gases at the same time can effectively improve the densification efficiency and uniformity of density distribution of carbon-carbon composite materials, promote the formation of a uniform rough layered structure, which is beneficial to improving the thermal conductivity of the carbon-carbon composite materials, and through high temperature and high pressure sintering, the density can be further increased.

[0012] Preferably, the density of the carbon-carbon blank is 0.8-1.6 g / cm 3 , preferably 0.85~1.55 g / cm 3 .

[0013] The inventors found that within the above preferred density range, the density is increased the most by the method of the present invention.

[0014] Preferably, the temperature of the graphitization treatment is 2400-3000°C, preferably 2400-2500°C.

[0015] The inventors found that a graphitization treatment before high temperature and high pressure can improve the degree of graphitization, optimize the structure of the pores in the carbon-carbon blank, improve the sealing phenomenon, and facilitate the creep densification of the matrix carbon during subsequent high temperature and high pressure sintering.

[0016] Preferably, the temperature of the high temperature and high pressure sintering is 2000~3000 ℃, the holding time is 1~30 h, the heating rate is 5~200 ℃ / min, and the pressure applied to the carbon-carbon composite blank is 20~100 MPa. In the present invention, the pressure of high temperature and high pressure needs to be effectively controlled. If the pressure is too high, it will cause the mold to break; if the pressure is too low, the graphitized blank cannot creep and the densification effect cannot be achieved.

[0017] Further preferably, the temperature of the high temperature and high pressure sintering is 2100-2300° C., the holding time is 1-2 h, the heating rate is 80-120° C. / min, and the pressure applied to the carbon-carbon composite blank is 20-100 MPa, preferably 50-70 MPa.

[0018] Preferably, during the high temperature and high pressure sintering process, protective gas is introduced throughout the process and the gas pressure in the furnace is maintained at 0-10 KPa.

[0019] The preparation method of the present invention comprises subjecting a carbon fiber preform to chemical vapor infiltration pyrolysis carbon densification and graphitization heat treatment in sequence to obtain a low-density carbon-carbon composite material after graphitization, and then subjecting the preform to high-temperature and high-pressure sintering. The creep of the matrix carbon during the high-temperature and high-pressure sintering process finally achieves the purpose of densifying the carbon-carbon composite material.

[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0021] (1) The densification method of the present invention has the advantages of simple process, convenient operation, short preparation cycle and low production cost;

[0022] (2) The densification method of the present invention causes little damage to the material and does not introduce impurities, thus providing a practical and effective method for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a SEM image of the cross section of the carbon-carbon composite material before sintering in Example 2,

[0024] Figure 2 This is a SEM image of the cross section of the carbon-carbon composite material after sintering in Example 2. DETAILED DESCRIPTION

[0025] The present invention provides a method for densifying a carbon-carbon composite material. The technical solution of the present invention is further described in detail below in conjunction with specific examples and drawings, but it should not be construed as limiting the protection scope and implementation methods of the present invention.

[0026] Example 1

[0027] The carbon fiber preform was densified by chemical vapor infiltration pyrolysis carbonization. During the pyrolysis carbonization process, the carrier gas was argon, the carbon source gas was propylene and methane, the volume ratio of the carrier gas to the carbon source gas was 3:1, and the ratio of propylene to methane was 0.08:1. The temperature of chemical vapor infiltration pyrolysis carbonization was 1100 °C and the furnace pressure was 2 KPa until the density of the densified carbon was 1.55 g / cm 3 The carbon-carbon body is prepared without graphitization heat treatment. The carbon-carbon body and the mold are assembled and placed in a sintering furnace. The furnace is evacuated to below 10 Pa and argon gas is introduced. The pressure in the furnace is controlled at 3-8 KPa. The pressure applied to the sample is 60 MPa. The heating rate is set at 100 ℃ / min. After heating to 2200 ℃, the temperature is kept for 1 h. After the temperature is kept, the sample is cooled to room temperature with the furnace.

[0028] The density of the sintered carbon-carbon composite material is 1.61 g / cm3 , the density increase rate is 4%. The density of the carbon-carbon composite material prepared in this embodiment has been improved, indicating that the matrix carbon has undergone a certain creep. Under the same conditions of other processes, graphitization treatment is carried out in an argon atmosphere, the graphitization treatment temperature is controlled to be 2400 ℃, the graphitization treatment time is 2 h, and the density of the carbon-carbon composite blank after graphitization treatment is 1.71 g / cm 3 The density increase rate is 10%, which means that graphitization heat treatment is beneficial to the high-temperature creep of the matrix carbon and has a better densification effect. This is because graphitization heat treatment can increase the gas renewal rate in the pore channels of the preform, change the pore structure, and alleviate the sealing phenomenon caused by chemical vapor infiltration. This may bring better densification effect for the creep of the matrix carbon during high-temperature and high-pressure sintering.

[0029] Example 2

[0030] The carbon fiber preform was densified by chemical vapor infiltration pyrolysis carbonization. During the pyrolysis carbonization process, the carrier gas was argon, the carbon source gas was propylene and methane, the volume ratio of the carrier gas to the carbon source gas was 3:1, and the ratio of propylene to methane was 0.08:1. The temperature of chemical vapor infiltration pyrolysis carbonization was 1100 °C and the furnace pressure was 2 KPa until the density of the densified carbon was 1.35 g / cm 3 The carbon-carbon blank was graphitized; the graphitization treatment was carried out under argon atmosphere, the graphitization temperature was controlled to be 2400 ℃, the graphitization time was 2 h, the carbon-carbon composite blank and the mold were assembled, put into the sintering furnace, evacuated to below 10 Pa, argon was introduced, the pressure in the furnace was controlled at 3~8 KPa, the pressure applied to the sample was 60 MPa, the heating rate was set to 100 ℃ / min, and the temperature was raised to 2200 ℃ and then the heat preservation was started. The heat preservation time was 1 h, and the furnace was cooled to room temperature after the heat preservation was completed.

[0031] The density of the densified carbon-carbon composite material is 1.50 g / cm 3 The density increase rate is 11%, indicating that the matrix carbon has undergone a certain creep, bringing a more obvious densification effect.

[0032] Figure 1 is a SEM image of the cross section of the carbon-carbon composite material before sintering in Example 2. Figure 2 This is a SEM image of the cross section of the carbon-carbon composite material after sintering in Example 2. It can be seen from the figure that after high temperature and high pressure sintering, the mesh layer of the carbon-carbon composite material has no large pores, the porosity of the needle-punched layer is significantly reduced, the densification effect is good, and no deformation of the carbon fiber is found, indicating that the densification process of the present invention has little damage to the fiber.

[0033] Example 3

[0034] The carbon fiber preform was densified by chemical vapor infiltration pyrolysis carbonization. During the pyrolysis carbonization process, the carrier gas was argon, the carbon source gas was propylene and methane, the volume ratio of the carrier gas to the carbon source gas was 3:1, and the ratio of propylene to methane was 0.08:1. The temperature of chemical vapor infiltration pyrolysis carbonization was 1100 °C and the furnace pressure was 2 KPa until the density was 0.85 g / cm 3 The carbon-carbon blank was subjected to graphitization heat treatment; graphitization treatment was carried out under argon atmosphere, the graphitization treatment temperature was controlled to be 2400 ℃, the graphitization treatment time was 2 h, the carbon-carbon composite blank and the mold were assembled, put into the sintering furnace, vacuumed to below 10 Pa, argon was started to be introduced, the gas pressure in the furnace was controlled at 3~8 KPa, the pressure applied to the sample was 60 MPa, the heating rate was set to 100 ℃ / min, and the temperature was raised to 2200 ℃ and then the heat preservation was started, the heat preservation time was 1 h, and the furnace was cooled to room temperature after the heat preservation was completed.

[0035] The density of the densified carbon-carbon composite material is 1.02 g / cm 3 The density increase rate is 20%. Since the carbon-carbon composite material before sintering has a low density and high porosity, high temperature and high pressure sintering causes pore compression and creep of matrix carbon, bringing about a significant densification effect.

[0036] Comparative Example 1

[0037] The carbon fiber preform was densified by chemical vapor infiltration pyrolysis carbonization. During the pyrolysis carbonization process, the carrier gas was argon, the carbon source gas was propylene and methane, the volume ratio of the carrier gas to the carbon source gas was 3:1, and the ratio of propylene to methane was 0.08:1. The temperature of chemical vapor infiltration pyrolysis carbonization was 1100 °C and the furnace pressure was 2 KPa until the density of the densified carbon was 1.81 g / cm 3 The carbon-carbon blank was subjected to graphitization heat treatment; graphitization treatment was carried out under argon atmosphere, the graphitization treatment temperature was controlled to be 2400 ℃, the graphitization treatment time was 2 h, the carbon-carbon composite blank and the mold were assembled, put into the sintering furnace, vacuumed to below 10 Pa, argon was started to be introduced, the gas pressure in the furnace was controlled at 3~8 KPa, the pressure applied to the sample was 60 MPa, the heating rate was set to 100 ℃ / min, and the temperature was raised to 2200 ℃ and then the heat preservation was started, the heat preservation time was 1 h, and the furnace was cooled to room temperature after the heat preservation was completed.

[0038] The density of the densified carbon-carbon composite material is 1.82 g / cm 3 The density increase rate is 0.55%. The density increase of the densified carbon-carbon composite material prepared in this embodiment is small. This is because the carbon-carbon composite material before sintering has a high density and low porosity. Compared with the low-density carbon-carbon composite material, the density increase is small, but it can be further densified by increasing the sintering temperature and extending the insulation time.

[0039] Comparative Example 2

[0040] The carbon fiber preform was densified by chemical vapor infiltration pyrolysis carbonization. During the pyrolysis carbonization process, the carrier gas was argon, the carbon source gas was methane, and the volume ratio of the carrier gas to the carbon source gas was 3:1. The temperature of chemical vapor infiltration pyrolysis carbonization was 1100 °C and the furnace pressure was 2 KPa until the density of the densified carbon was 1.36 g / cm 3 The carbon-carbon blank was subjected to graphitization heat treatment; graphitization treatment was carried out under argon atmosphere, the graphitization treatment temperature was controlled to be 2400 ℃, the graphitization treatment time was 2h, the carbon-carbon composite blank and the mold were assembled, put into the sintering furnace, vacuumed to below 10 Pa, argon was started to be introduced, the gas pressure in the furnace was controlled at 3~8 KPa, the pressure applied to the sample was 60 MPa, the heating rate was set to 100 ℃ / min, and the temperature was raised to 2200 ℃ and then the heat preservation was started, the heat preservation time was 1 h, and the furnace was cooled to room temperature after the heat preservation was completed.

[0041] The density of the densified carbon-carbon composite material is 1.42 g / cm 3 The density improvement rate is 4%. Compared with Example 2, only the carbon source of the chemical vapor infiltration pyrolytic carbon is changed in this example, and a single methane gas is used. The density improvement rate of Example 2 is significantly higher than that of this example because adding an appropriate amount of propylene to methane can improve the uniformity of density distribution, which is beneficial to the generation of a rough layer structure pyrolytic carbon with a higher degree of graphitization. The addition of propylene is also beneficial to avoid the structural unevenness problem caused by a single carbon source, which is beneficial to the creep densification of the matrix carbon during the high temperature and high pressure sintering process.

Claims

1. A method for densifying a carbon-carbon composite material, characterized in that: The carbon fiber preform is subjected to chemical vapor infiltration and pyrolysis carbon densification to obtain a carbon-carbon blank, the carbon-carbon blank is subjected to graphitization to obtain a carbon-carbon composite blank, and the carbon-carbon composite blank is subjected to high temperature and high pressure sintering to obtain a carbon-carbon composite material.

2. A method for densifying a carbon-carbon composite material according to claim 1, characterized in that: The temperature of chemical vapor infiltration pyrolytic carbon densification is 900~1500℃, and the furnace pressure is 0.3~4.0 Kpa.

3. A method for densifying a carbon-carbon composite material according to claim 1 or 2, characterized in that: The carrier gas for chemical vapor infiltration pyrolysis carbon densification is argon, and the carbon source gas is propylene and / or methane, wherein the volume ratio of the carrier gas to the carbon source gas is 1-4:

1.

4. A method for densifying a carbon-carbon composite material according to claim 3, characterized in that: When the carbon source gases are propylene and methane, the volume ratio of propylene to methane is 0.05-0.2:

1.

5. A method for densifying a carbon-carbon composite material according to claim 1 or 2, characterized in that: The density of the carbon-carbon blank is 0.8-1.6 g / cm 3 .

6. A method for densifying a carbon-carbon composite material according to claim 1 or 2, characterized in that: The temperature of graphitization treatment is 2400~3000℃.

7. A method for densifying a carbon-carbon composite material according to claim 1 or 2, characterized in that: The temperature of the high temperature and high pressure sintering is 2000-3000°C, the holding time is 1-30 h, the heating rate is 5-200°C / min, and the pressure applied to the carbon-carbon composite blank is 20-100 MPa.

8. The method for densifying a carbon-carbon composite material according to claim 7, characterized in that: During the high temperature and high pressure sintering process, protective gas is introduced throughout the process, and the gas pressure in the furnace is maintained at 0-10 KPa.

Citation Information

Patent Citations

  • Method for rapidly densifying high-density full-gaseous phase pyrolytic carbon-based carbon / carbon composite materials

    CN101913896A

  • Carbon fiber, preparation method thereof and composite material

    CN116876203A

  • Carbon-carbon composite material as well as preparation method and application thereof

    CN117865709A

  • Method for preparing automotive brake disc made of c / c-sic composite material

    WO2020024973A1